Penerapan model pembelajaran berbasis masalah untuk meningkatkan kemampuan pemecahan masalah matematika pada materi vektor di kelas X MIA-1 SMA Negeri 18 Medan - Silaban, Elita Erawati (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to improve the ability of mathematical problem solving on the subject of vector in class X MIA-1 SMA Negeri 18 Medan through Problem-Based Learning model. This type of research is classroom action research conducted in 2 cycles, cycle I consists of 2 meetings and cycle II consists of 2 meetings. Subjects in this study are all students of class X MIA-1 SMA Negeri 18 Medan in the even semester of the academic year 2016/2017 which amounted to 38 people. The object of this research is the problem solving ability of mathematics students by applying the model of Problem Based Learning on vector material in class X MIA-1 SMA Negeri 18 Medan. Based on data analysis after giving of action in cycle I through the test of problem solving ability of mathematics I obtained 10 students (26,32%) from 38 students have reached learning mastery (value ≥ 70) with grade average 24,21. Giving action in cycle II through test of problem solving ability of mathematics II obtained 34 students (89,47%) from 38 students have reached mastery learning (value ≥ 70) with grade average 80,25. From cycle I and cycle II, the number of students who achieved learning completeness is 24 students (63,16%) and the average value is 56,04. Based on the observations made by the observer, obtained learning management conducted by researchers in cycle I included in either category. In cycle II, the level of ability of the researcher to manage the learning is good. Thus it can be said that the class has met 85% of students’ learning completeness criteria. Based on the results of this study can be concluded that there is an increase in problem solving skills of mathematics students class X MIA-1 SMA Negeri 18 Medan T.A 2016/2017 so that learning by using Problem-Based Learning model can be used as an alternative learning.